Constructs in Leadership Style's Choice based on Workplace Experience in Ugandan Secondary Schools - Olive Kimbowa Nansubuga; Charles Muweesi; Lan Zhao; Abubaker Mutebi (Foxton Books, 2019)
This qualitative study was done on the head teacher's choice of leadership styles and their implication for better performance using one selected Private school in Mukono District (Uganda). It established that, head teacher's choice of leadership styles did not cause any hindrances amongst his staff so they worked harmoniously to achieve the set targets and goals, motivational-skills and team playing-role in all that happens in the school fosters active participation of all stake holders which eventually leads to attainment of results as targeted, thus recommending for effective delivery of quality education services and improved students' academic performance is to be attained.